2009
DOI: 10.1152/physiolgenomics.00116.2009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for exercise training responses in FVB/NJ and C57BL/6J mice

Abstract: Massett MP, Fan R, Berk BC. Quantitative trait loci for exercise training responses in FVB/NJ and C57BL/6J mice. Physiol Genomics 40: 15-22, 2009. First published September 29, 2009 doi:10.1152/physiolgenomics.00116.2009.-The genetic factors determining the magnitude of the response to exercise training are poorly understood. The aim of this study was to identify quantitative trait loci (QTL) associated with adaptation to exercise training in a cross between FVB/NJ (FVB) and C57BL/6J (B6) mice. Mice completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 67 publications
4
57
0
Order By: Relevance
“…Thus, understanding of the mechanisms underlying the between strain differences at baseline could also explain some of the difference in the degree of adaptation to training. This assumption was consistent with observation of an overlap between QTL affecting pre-and post-training endurance in both mice (Massett et al, 2009) and humans (Rico-Sanz et al, 2004).…”
Section: Endurance Capacitysupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, understanding of the mechanisms underlying the between strain differences at baseline could also explain some of the difference in the degree of adaptation to training. This assumption was consistent with observation of an overlap between QTL affecting pre-and post-training endurance in both mice (Massett et al, 2009) and humans (Rico-Sanz et al, 2004).…”
Section: Endurance Capacitysupporting
confidence: 92%
“…Therefore, this relatively small difference in accumulated training time cannot explain the nonresponder strains. Instead, these findings together with the results of the mapping of quantitative trait loci (QTL) support the importance of genetic variation in adaptation to training (Massett et al, 2009). More importantly, our observation indicated that nonresponder strains were also poor performers at the baseline.…”
Section: Endurance Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The test is a modification of the protocol described earlier (Knab et al, 2009; Massett et al, 2009). The starting speed of the treadmill at a zero incline was set at 16.8 m/min.…”
Section: Methodsmentioning
confidence: 99%
“…Based on significant strain differences in baseline or pre-training exercise capacity measured during a graded treadmill test, quantitative trait loci (QTL) for exercise capacity have been identified in rats and mice [ 17 21 ]. In addition, a genome wide linkage scan for exercise capacity and responses to training was performed using in an F 2 population derived from inbred FVB/NJ (FVB) and C57BL/6J (B6) mice [ 20 ]. In (FVB x B6) F 2 population, several significant and suggestive QTL for pre- and post-training exercise capacity and the responses to training (i.e., change in exercise capacity) were identified.…”
Section: Introductionmentioning
confidence: 99%